Muhammadiyah Environmental Ethics to Realize Green Campus: Case Study at The University of Muhammadiyah Malang - Susilo, RKD; Arrozy, A; ., Suwignyo (KnE Social Sciences, 2023)
This research explains the campus’ efforts to realize a green campus in response to the crucial issues of the environmental crisis that has been rife recently, both related to the water resource crisis, disasters, and the transition to clean energy. For this reason, all parties are encouraged to take steps to explore all ecological resources, including environmental ethics based on Islamic values and the campus world. The methodology used is a qualitative approach with a case study approach. Data collection techniques are collected through interviews, observations, and document studies. Sampling is carried out by purposive sampling to the implementers of water resource conservation activities at UMM, both centers for environmental and population studies, renewable energy infrastructure, and implementers of the Islamic and Muhammadiyah community program. The research findings state that water resource conservation activities have been carried out by UMM. Conservation includes the utilization and maintenance of water resources. This condition benefits from the UMM landscape, where rivers, water sources, and ponds exist. Ecological practices, these practices give birth to principles of environmental ethics such as conservation, creativity, beauty, sustainability, and benefit. But the formulation of this ethic still requires more inclusive follow-up measures. Keywords: environmental ethics, community, conservation